Application of Hypothetical Ecological Risk Analysis to Sustainable Usage of Possible Winter Recreation Areas in Seyhan Basin (Türkiye) - Okan Yeler; Gazel Burcu Aydın; Belgin Çamur Elipek; Süha Berberoğlu (Aquatic Sciences and Engineering)
In this study, the long-term suitability of the area proposals for winter recreation activities in the Seyhan Basin (Türkiye), which is located in the Mediterranean and Central Anatolia regions and includes a large part of the Taurus Mountains, were examined ecologically. For this purpose, the predicted global warming scenarios in the basin and the anthropogenic impacts arising from the planned recreation areas were evaluated for the upper basin (recreation areas) and lower basin (water resources, agricultural lands, and settlements) using a hypothetical risk analysis. For this purpose, multispectral images were obtained by using Landsat 8 Oli Multispectral images of the snow areas in the region in January-February-March 2019, and a hypothetical ecological risk analysis was created considering a total of 5 pressure factors originating from global climate change and anthropogenic effects. These possible factors were determined as flood (S1), drought (S2), sedimentation (S3), aquatic nutrients (S4), and tourist density (S5). The effects of these factors on a total of four features (C1: water quality, C2: fauna-flora, C3: agricultural areas, and C4: settlements) in the region were evaluated by hypothetical grading based on the literature. According to the hypothesis results obtained by the formula and statistical calculations, it was determined that the flood factor (S1) that will occur due to possible snow melt due to global climate change in the winter recreation areas in the studied region is the most significant factor limiting the sustainable usage of the Basin. For this reason, it has been emphasized in this study that the possibility of regions being exposed to the effects of climate change in the future should be taken into account, especially when planning for winter recreation areas. At the end of this study, it was concluded that the ecological balance analysis of basins is important, especially in terms of ensuring the long-term sustainable use of winter recreation areas.